Flexible, Semitransparent, and Inorganic Resistive Memory based on BaTi0.95 Co0.05 O3 Film - Yang, Yuxi (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.